The Relationship Between Obtaining the Academic Accreditation and Quality of Academic Performance: A Comparative Study - Al-Shamrani, Ghada bint Shahir bin Hazaa (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the relationship between obtaining the academic accreditation and quality of academic performance with respect to some elements of the quality related to the students and faculty members as the most important elements of the inputs and outputs of the educational process. This study was conducted on faculty members in six of the scientific colleges at King Saud University in Riyadh, three of them obtained the accreditation and three of them did not. A Quotas sample has been withdrawn consisted of 296 single, where a questionnaire was distributed. The volume of responses was 246 weighing 83%. The study found out that (67.9 %) of the respondents in the colleges that received accreditation believes that there is a development in the quality of academic performance in college after obtaining the academic accreditation. The study also showed that (62.2 %) of the respondents in colleges who obtained the accreditation or did not obtain it believes that obtaining the accreditation necessarily leads to a quality in academic performance. As it turns out from the study that there is no relationship between obtaining academic accreditation and the quality of students that is, to obtain accreditation does not necessarily lead to quality learning outcomes of students, where it turns through the views of the respondents that the quality of the outputs of the educational process of students in colleges did not receive the accreditation is higher than in colleges obtained it. The results also showed that there is no relationship between obtaining an academic accreditation and quality performance among faculty members, it became clear that the faculty members in colleges who obtained the accreditation or did not obtain it agree on the quality of the performance of a faculty member.